2011
DOI: 10.1186/1472-6963-11-170
|View full text |Cite
|
Sign up to set email alerts
|

Are waiting times for hospital admissions affected by patients' choices and mobility?

Abstract: BackgroundWaiting times for elective care have been considered a serious problem in many health care systems. A topic of particular concern has been how administrative boundaries act as barriers to efficient patient flows. In Norway, a policy combining patient's choice of hospital and removal of restriction on referrals was introduced in 2001, thereby creating a nationwide competitive referral system for elective hospital treatment. The article aims to analyse if patient choice and an increased opportunity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…For example, a study among Somali women in Norway shows that despite the women's good knowledge of diabetes and risk factors such as sedentary lifestyle and unhealthy diet, they faced barriers to being physically active, such as time pressure, a lack of financial affordability for training facilities, and an absence of a tailored physical activity environment, such as training facilities not being gender-exclusive (Gele, Torheim, Pettersen, & Kumar, 2015). A similar study on barriers to outdoor physical activity among Somali youth, pointed out financial barriers such as expensive outdoor clothing, lack of time because of parents' work and children having afterschool jobs (Rothe et al, 2010). In light of this, to gain a fuller picture of migrants' healthcare consumption, financial barriers should include consideration of both direct and indirect costs that prevent access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study among Somali women in Norway shows that despite the women's good knowledge of diabetes and risk factors such as sedentary lifestyle and unhealthy diet, they faced barriers to being physically active, such as time pressure, a lack of financial affordability for training facilities, and an absence of a tailored physical activity environment, such as training facilities not being gender-exclusive (Gele, Torheim, Pettersen, & Kumar, 2015). A similar study on barriers to outdoor physical activity among Somali youth, pointed out financial barriers such as expensive outdoor clothing, lack of time because of parents' work and children having afterschool jobs (Rothe et al, 2010). In light of this, to gain a fuller picture of migrants' healthcare consumption, financial barriers should include consideration of both direct and indirect costs that prevent access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a need for evidence-based knowledge about the different migrant groups' propensity to use healthcare services based on cultural and socioeconomic background, but we also need to know about the quality of healthcare individual persons with migrant backgrounds receive. For example, there is evidence of longer waiting times for hospital treatment for patients with low levels of education and/or income than for groups higher up the socioeconomic scale (Monstad, Engesaeter, & Espehaug, 2014;Ringard & Hagen, 2011). All the same, although many of the newly arrived migrants from non-Western countries fit the general description, there is need for a differentiated research on various groups of migrants -from labour migrants to refugees and 'illegal' migrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, all patients were granted free choice of hospitals combined with the removal of county border barriers. This primarily aimed to reduce long waiting times, and previous research has shown that both the introduction of ABF and the expansion of hospital budgets have been factors in reducing waiting time for elective patients (Hagen & Kaarboe, 2006;Ringard & Hagen, 2011). Although these two initiatives may also have influenced the hospitals' operational performance, we conclude that physician productivity did not improve during our study period, irrespective of these reforms.…”
Section: At What Level Do Health Care Reforms Work?mentioning
confidence: 62%
“…This is an important ongoing issue, especially for publicly funded institutes. Although extensive research and discussion have been put forth, there is no panacea for this dynamic issue. If the length of waiting lists can be forecasted by reasonable statistical summaries, then hospitals may be able to better prepare and improve their service performance.…”
Section: Application To Hospital Waiting List Datamentioning
confidence: 99%